Solar dryers for tropical food preservation: Thermophysics of crops, systems and components. (15th September 2017) - Tomar, Vivek; Tiwari, G.N.; Norton, Brian
Highlights: It has been shown that solar dryer design selection and subsequent dryers process optimization in a particular climate are strongly dependent on the harvested crop characteristics and the final desired dried product attributes. The latter often extend beyond the safe storage moisture content to include nutritional, colour and texture/shrinkage qualities. Only by considering the dynamic behaviour of (i) crop drying behaviour and (ii) the specific weather conditions during drying can effective drying with minimal losses be achieved. Abstract: Drying reduces the moisture content of harvested crops thus slowing decay processes to enable longer-term storage. Solar dryers contain the crop being dried, to enhance solar energy collection incurring lower crop losses than are associated with open-sun drying and recurrent costs than are inherent to uses of fossil-fuels for drying. The influences of key environmental, operational and design parameters for solar dryers are discussed including: (i) psychrometry of drying processes and ambient conditions, (ii) how initial crop properties are converted to final desired product attributes, (iii) feasibility of using powered components such as fans and (iv) air-heating solar collector selection.